Manajemen Green Waqf Dalam Mitigasi Perubahan Iklim Tinjauan Tafsir Tematik Kontemporer - Mukhtar Yunus (Eshraq: Journal of Islamic Studies, 2025)
Climate change is a global challenge that increasingly threatens the sustainability of human life on Earth. Indonesia, as the country with the largest waqf potential in the world, possesses a strategic opportunity to integrate green waqf management as an instrument for climate change mitigation. This study analyzes the concept of green waqf from the perspective of a thematic exegesis (tafsir tematik) of the fasad fil-ardh (destruction on Earth) and istikhlaf (vicegerency/succession) verses in the Qur'an. Utilizing a qualitative research method with a thematic exegesis approach and literature review, this study finds that green waqf is a concrete implementation of the khalifah fil-ardh concept, which entails a responsibility for environmental preservation. The results indicate that effective green waqf management encompasses: (1) ecosystem-based waqf planning, (2) sustainable waqf asset management, (3) local community empowerment, and (4) environmental impact monitoring. This study recommends the development of a national green waqf policy integrated with Indonesia's 2030 Nationally Determined Contributions (NDC) targets.